The Advance of African Capital The Growth of Nigerian Private Enterprise. - Forrest, Tom (Edinburgh University Press, 1994)
Combining ethnographic and historical perspectives, this study is the most detailed, most extensive account of medium- and large-scale African business. Not only a valuable digest of business activities, this important study also challenges existing views about African enterprise and is highly relevant to policy-makers concerned with economic development.
Description based upon print version of record.
Keywords: Business enterprises -- Nigeria -- History -- 20th century.; Saving and investment -- Nigeria -- History -- 20th century.; Free enterprise -- Nigeria -- History -- 20th century.; Entrepreneurship -- Nigeria -- History -- 20th century.; Entreprises -- Nigeria -- Histoire -- 20e siècle.; Entrepreneuriat -- Nigeria -- Histoire -- 20e siècle.; Business enterprises; Entrepreneurship; Free enterprise; Saving and investment; Nigeria; 1900-1999; History